Fusion of multiscale wavelet-based fractal analysis on retina image for stroke prediction - Che Azemin, Mohd Zulfaezal; Kumar, Dinesh Kant; Wong, Tien Yin; Wang, Jie Jin; Kawasaki, Ryo; Mitchell, Paul; Arjunan, Sridhar P. (2010)
In this paper, we present a novel method of analyzing retinal vasculature using Fourier Fractal Dimension to extract the complexity of the retinal vasculature enhanced at different wavelet scales. Logistic regression was used as a fusion method to model the classifier for 5-year stroke prediction. The efficacy of this technique has been tested using standard pattern recognition performance evaluation, Receivers Operating Characteristics (ROC) analysis and medical prediction statistics, odds ratio. Stroke prediction model was developed using the proposed system.